Association between single nucleotide polymorphism-genotype and outcome of patients with chronic lymphocytic leukemia in a randomized chemotherapy trial. - Wade, R; Bernardo, D; Richards, S; Rossi, D; Crowther-Swanepoel, D; Gaidano, G; Oscier, D; Catovsky, D; Houlston, R (2011)
There is variability in the outcome of patients with chronic lymphocytic leukemia with apparently the same stage of disease. Identifying genetic variants that influence patients' outcome and response to treatment may provide important insights into the biology of the disease.